Correlation Between Pre-Transplant Anemia and Mortality After Kidney Transplantation in Diabetic and Non-Diabetic Patients - Dwi Lestari Partiningrum; Nusa Purnawan Putra; Lestariningsih Lestariningsih (Majalah Kedokteran Bandung, 2026)
Anemia is an established risk factor for mortality and graft failure among kidney transplant recipients, particularly those with diabetes mellitus; however, the combined effects of these conditions remains poorly understood. Regular anemia evaluation is important for patients with End-Stage Kidney Disease (ESKD), especially after transplantation. This retrospective study aimed to analyze 40 kidney transplant recipients with anemia to investigate the correlation between pre-transplant anemia and post-transplant mortality in diabetic and non-diabetic patients at Dr. Kariadi National General Hospital between 2014 and 2020. Data on patient demographics and comorbidities, as well as laboratory data were collected and analyzed. The mean patient age was 41.9±12.4 years, with male constituted 52.5%. The average pre-transplant hemoglobin and serum creatinine levels were 9.4±1.4 mg/dL and 12.4±18.9 g/dL, respectively. Diabetes mellitus was present in 12.5% of patients. Overall, the one-year and three-year post-transplant mortality rates were 20% and 22.5%, respectively. One-year post-transplant mortality occurred in 80% of diabetic patients and 11.4% of non-diabetic patients (p=0.003). At three years, mortality reached 80% in diabetic patients and 14.3% in non-diabetic patients (p=0.006). Pre-transplant anemia significantly increases the risk of post-transplant mortality, especially among diabetic patients, highlighting the need for optimal anemia management before kidney transplantation to enhance long-term patient outcomes.